The comparative study for the isotropic and orthotropic circular plates. (August 2016) - Popa, C; Tomescu, G
Abstract: The aim of study is static bending analysis of an isotropic circular plate using analytical method i.e. Classical Plate Theory, Finite Element software ANSYS and experimental methods. The diameter of circular plate, material properties, like modulus of elasticity (E), poissons ratio (µ) and intensity of loading is assumed at the initial stage of research work. In comparison with this plane plate we analyze a plate of same dimensions and charge, but having ribs, to see the advantage of the rigidify. The two plates are fixed supported subjected to uniformly distributed load.